A Multifunctional Artificial Interphase with Fluorine‐Doped Amorphous Carbon layer for Ultra‐Stable Zn Anode. (15th August 2022) - Wang, Han; Chen, Yuejiao; Yu, Huaming; Liu, Wen; Kuang, Guichao; Mei, Lin; Wu, Zhibin; Wei, Weifeng; Ji, Xiaobo; Qu, Baihua; Chen, Libao
Abstract: Building an artificial interphase layer for tackling uncontrollable Zn dendrites and serious side reactions is a highly desirable strategy, but it is often hampered by the limited Zn 2+ transport. Here, a stable fluorine‐doped amorphous carbon (CF) artificial layer is constructed on a Cu current collector (CF‐Cu) via facile carbonization treatment of a fluoropolymer coating to realize underlying Zn deposition. As evidenced experimentally and theoretically, this inorganic CF layer with ionic conductivity and electronic insulation successfully triggers dendrite‐free Zn deposition at the CF‐Cu interface with preferred Zn(002) crystal plane stacking parallel to the substrate surface, thus greatly promoting the inhibition of Zn‐dendrites and blocking of interfacial side reactions. The introduced fluorine atoms as abundant zincophilic sites play an important role in driving fast zinc‐ion transfer kinetics, which can partly convert into ZnF2 as an artificial solid Zn 2+ conductor to further guide uniform Zn deposition. Consequently, the CF‐Cu electrode enables high reversibility with 99% coulombic efficiency and a long cycling stability of 1900 cycles at 2 mA cm –2 . The integrated CF‐Cu@Zn anode achieves up to 2200 h cycles with a low voltage polarization. This study provides inspiration for the design of artificial interphase layers for stable nondendritic metal batteries. Abstract : A fluorine‐doped amorphous carbon layer is developed on Cu foil as a multifunctional artificial interphase. The interphase regulates the uniform Zn 2+ flux and triggers fast Zn 2+ transfer kinetics for realizing the underlying deposition of Zn metal, as well as promotes flat Zn growth for further inhibition of side reactions. Highly stable Zn batteries are achieved via this "sandwich" anode.